GENERALIZED HYERS-ULAM STABILITY OF MIXED TYPE ADDITIVE QUADRATIC FUNCTIONAL EQUATION OF RANDOM DERIVATION IN RANDOM NORMED ALGEBRAS. - Alshybani, Shaymaa (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2020)
By the fixed point method, I have proved the generalized stability of the random derivation of the following additive–quadratic functional equation f(x+2y)+f(x+y)+f(y-x)=f(2x+y)-f(x)+4f(y)+f(-y) in random normed algebras.